K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 4 2016

S=\(1-2+2^2-2^3+2^4-2^5+...+2^{2014}-2^{2015}\)

2S=2-\(2^2-2^4+2^5+...+2^{2015}-2^{2016}\)

2S+S=1-22016

3S=1-22016

1-3S=22016

mà 1-3S=2x

nên x=2016

11 tháng 1 2016

S=22016 -1

 

26 tháng 3 2017

\(TA-CO':\)

\(A=\frac{4+\frac{7}{2014}-\frac{7}{2015}+\frac{7}{2012}-\frac{7}{2013}}{7+\frac{7}{2014}-\frac{7}{2015}+\frac{7}{2012}-\frac{7}{2013}}\)

\(A=\frac{4\left(\frac{1}{2014}-\frac{1}{2015}+\frac{1}{2012}-\frac{1}{2013}\right)}{7\left(\frac{1}{2014}-\frac{1}{2015}+\frac{1}{2012}-\frac{1}{2013}\right)}\)

\(A=\frac{4}{7}\)

\(B=\frac{1+2+...+2^{2013}}{2^{2015}-2}\)

ĐẶT \(C=1+2+...+2^{2013}\)

\(\Rightarrow2C=2+2^2+...+2^{2014}\)

\(\Rightarrow2C-C=\left(2+2^2+...+2^{2014}\right)-\left(1+2+...+2^{2013}\right)\)

\(\Rightarrow C=2^{2014}-2\)

\(\Rightarrow B=\frac{2^{2014}-1}{2^{2015}-2}\)

\(B=\frac{2^{2014}-1}{2\left(2^{2014}-1\right)}\)

\(B=\frac{1}{2}\)

\(\Rightarrow A-B=\frac{3}{7}-\frac{1}{2}=\frac{6}{14}-\frac{7}{14}\)

\(A-B=\frac{6-7}{14}=\frac{-1}{14}\)

VẬY, \(A-B=\frac{-1}{14}\)

31 tháng 10 2020

\(S=1-2+2^2-2^3+...+2^{2012}\)

\(2S=2-2^2+2^3-2^4+...+2^{2015}\)

\(3S=1+2^{2015}\)

\(\Rightarrow3S-2^{2015}=1+2^{2015}-2^{2015}=1\)

vậy.........